(untitled) (Plant Tissue Culture and Biotechnology, 2021)
Bambusa balcooa Roxb. was in vitro propagated by optimizing protocol using nodal segment from secondary branches with 100% success in MS liquid media containing 100 mg/l Myo-inositol, 3% sucrose supplement with 4.4 - 26.64 μM BAP for shoot multiplication, and 2.69 - 32.26 μM NAA for root induction. The highest shoot multiplication (14.53 ± 0.33 folds), shoot length (5.9 ± 0.6 cm), shoot number per explants (4.0 ± 0.24), and rooting (89.3 ± 0.33%) was obtained in MS liquid media supplement with 13.32 μM BAP (shooting) and 26.88 μM NAA (rooting) and 1% aqueous leaf extract of Artemisia vulgaris L. (EAV). Twenty RAPD (Random amplified Polymorphic DNA) primers were used individually to amplify DNA of tissue culture-raised plants and the mother plant where 8 primers yielded monomorphic banding patterns with reproducible, clear, scorable bands (2.8 per primer) ranging from 250 to 1800 bp respectively which revealed the micropropagated plants of B. balcooa retained their genetic stability. Plant Tissue Cult. & Biotech. 31(1): 81-95, 2021 (June)